Study on the Optimal Surgical Scheme for Very Severe Osteoporotic Vertebral Compression Fractures. Issue 2 (29th November 2022) - Wen, Zhenxing; Mo, Xiaoyi; Ma, Hangzhan; Li, Haonan; Liao, Changhe; Fu, Dan; Cheung, Wing Hoi; Qi, Zhichao; Zhao, Shengli; Chen, Bailing
Abstract : Objective: Therapy of very severe osteoporotic compression fractures (VSOVCF) has been a growing challenge for spine surgeons. Opinions vary regarding the optimal surgical procedure for the treatment of VSOVCF and which internal fixation method is more effective is still under debate, and research on this topic is lacking. This retrospective study was conducted to compare the efficacy and safety of various pedicle screw fixation methods for treating VSOVCF. Methods: This single‐center retrospective comparative study was conducted between January 2015 and September 2020. Two hundred and one patients were divided into six groups according to different surgical methods: 45 patients underwent long‐segment fixation (Group 1); 39 underwent short‐segment fixation (Group 2); 30 received long‐segment fixation with cement‐reinforced screws (Group 3); 32 received short‐segment fixation with cement‐reinforced screws (Group 4); 29 had long‐segment fixation combined with kyphoplasty (PKP) (Group 5); and 26 cases had short‐segment fixation combined with PKP (Group 6). The clinical records were reviewed and the visual analogue scale (VAS) score and the Oswestry Disability Index (ODI) score were used for clinical evaluation. The vertebral height (VH), fractured vertebral body height (FVBH), and Cobb's angle were objectively calculated and analyzed on lateral plain radiographs. Student's t ‐tests and one‐way ANOVA among groups were conducted to analyze the continuous, and the chi‐squared test was used to compare the dichotomous or categorical variables. The difference was considered statistically significant when the P ‐value was less than 0.05. Results: The six groups had similar distributions in age, gender, course of the disease, follow‐up period, and injured level. In the postoperative assessment of the VAS score, the surgical intervention most likely to rank first in terms of pain relief was the short‐segment fixation with cement‐reinforced screws (Group 4). For the functional evaluation, the surgical intervention that is most likely to rank first in terms of ODI score was a short‐segment fixation with cement‐reinforced screws (Group 4), followed by long‐segment fixation (Group 1). The long‐segment fixation with cement‐reinforced screws was the first‐ranked surgical intervention for the maintenance of Cobb's angle and vertebral height, whereas the short‐segment fixation performed the worst. The highest overall complication rate was in Group 6 with an incidence of 42.3% (11/26), followed by Group 2 with an incidence of 38.5% (15/39). Conclusion: For the treatment of VSOVCF, the short‐segment fixation with cement‐reinforced screws is the most effective and optimal procedure, and should be used as the preferred surgical method if surgeons are proficient in using cemented screws; otherwise, directly and unquestionably use long‐segment fixation to achieve satisfactory clinical results. Abstract : Opinions vary regarding the optimal surgical procedure for treating VSOVCF. By comparing different surgical methods, we concluded that short‐segment fixation with cement‐reinforced screws is the optimal procedure, and could be used first if surgeons are proficient in using cemented screws; otherwise, long‐segment fixation is unquestionably used to achieve surgical goals.